Estrategias de comunicación digital e impacto de la red social Facebook del Gobierno Autónomo Descentralizado Parroquial Santa Rosa, en los ciudadanos periodo diciembre 2021 – febrero 2022 - Tenelema Toscano, Rosa Yessenia (2023)
The research project focuses on identifying the communicational reality of Santa Rosa Parish Decentralized Autonomous Government, for that reason a descriptive and field research was applied in order to collect the necessary data to carry out the analysis of the current situation. In addition, a mixed qualitative and quantitative approach was used to collect information such as a survey, interview and observation sheet. The researchers, seeing the moderately good reception, that is, a greater increase in followers and more interaction in the networks, decide to create an Annual Operational Plan of digital Communication Strategies, thanks to current communication models and new technologies, with all This is clear and after a long investigation, certain problems were identified when communicating the activities carried out by the Santa Rosa Parish GAD for the citizens. The survey was applied to a total sample of 370 inhabitants of the parish. Based on the results, it was identified that the citizens of Santa Rosa frequently use the Facebook Social Network to stay informed of daily events. However, there is a disorganization when publishing content on the fan page and the design of the annual operating plan of strategies was essential to promote responsibility and planning, through this support the positioning of the image according to the needs of the institution will be achieved. Keywords: Communication strategies, Facebook Social Network, Communication